Plan de implementación para la producción de canilleras personalizadas - Carrión Jaramillo, Pedro Lorenzo (2015)
Shin guards are a simple and essential product to the practice soccer, this sports article represents a small income margin in major sports brands economies. The lack of innovation and development of this product has made it be relegated to becoming a gloomy product where the consumer is satisfied with the few options that the market offers. Knemis looking to offer soccer consumer an innovative, comfortable and personalized product made for the consumer by the consumer. There is a social trend worldwide for customized sports equipment like shoes that differ from the rest. Knemis seeks to exploit this trend by offering customized shin guards with a unique design and fit...